Cover Feature: Oxygen‐ and Sulfur‐bridged L‐shaped π‐Conjugated Molecules: Synthesis, Aggregated Structures, and Charge Transporting Behavior (Asian J. Org. Chem. 11/2018). Issue 11 (19th October 2018) - Okamoto, Toshihiro; Dosei, Hiroaki; Mitani, Masato; Murata, Yoshinori; Ishii, Hiroyuki; Nakamura, Ken‐ichi; Yamagishi, Masakazu; Yano, Masafumi; Takeya, Jun
Abstract : A series of oxygen‐ and sulfur‐bridged L‐shaped π‐electron cores with Cs symmetry, dinaphtho[2, 1‐ b :2′, 3′‐ d ]furan (DNF–L) and dinaphtho[2, 1‐ b :2′, 3′‐ d ]thiophene (DNT–L), have been designed and investigated. DNF–L and DNT–L were successfully synthesized from commercially available 2‐methoxylnaphthalene in three and four steps, respectively. Notably, these compounds exhibited high solubilities in common organic solvents and excellent thermal and chemical stabilities. Moreover, DNF–L shows a charge carrier mobility of up to 1.5 cm 2 /Vs in single‐crystal transistors. More information can be found in the Full Paper by Toshihiro Okamoto, Masafumi Yano et al. onpage 2309 in Issue 11, 2018 (DOI:10.1002/ajoc.201800403 ).